Swedish journalists' perceptions of legal protection against unlawful online harassment - Oscar Björkenfeldt (Frontiers in Sociology, 2023)
This study examined journalists' perceptions regarding the legal system's ability to protect them against online harassment. By utilizing open-ended survey responses from respondents with varying levels of trust in the legal system, the findings suggested a need for increased technical proficiency, resources, and priority within the legal system to adequately address the issue. Additionally, a reciprocal relationship between the normalization of online harassment within the journalistic profession and the legal system's commitment to providing protection was identified. However, the study also found that when the legal system's mediated approach to online harassment is positive, it affects attitudes and norms relating to legal protection. Consequently, it reveals a unique insight into how journalists respond to the message conveyed by fair treatment and respect from the legal system. Notably, this result implies that when such messages are internalized, journalists feel more empowered to take measures against online harassment. As a result of this analysis, I propose that current laws should be implemented more effectively and that policy strategies should be developed to positively influence social norms and social control to bolster journalistic autonomy and freedom of speech in the digital age.